The impact of using social media on marketing orientation An applied study in a sample of commercial markets in Sulaymaniyah Governorate - Soran Hama Saeed Hama Saleh; Shilan Fazil Mahmoud (The Scientific Journal of Cihan University– Sulaimaniya, 2019)
The aim of the research is to examine the impact of using social media through its dimensions such as Facebook, Mobile, YouTube in the marketing orientation, where the research community represents the owners of marketing shops in large markets who uses social media to reach customers, the questionnaire was distributed to a sample of shops in a huge market in order to reach the people who uses the social networking network in their marketing operations. The total questionnaires were completed (10) questionnaire. The researchers used the research in the descriptive method HLI also used the statistical program Spss to analyze the search data. The research concluded with several results, the most important one is the presence of statistical significance for the dimensions of social communication (Facebook, mobile, YouTube) on the marketing orientation by the dimension "customer orientation and market excellence". The importance of the research is adopting the large markets through the use of social media in marketing their products will help them compete and achieve market excellence in their work.